1965
DOI: 10.1111/j.1476-5381.1965.tb01799.x
|View full text |Cite
|
Sign up to set email alerts
|

METABOLISM OF [14C]‐NEOSTIGMINE IN THE RAT

Abstract: When neostigmine is administered orally to patients with myasthenia gravis two metabolites are excreted in the urine one of which has been identified as m-hydroxyphenyltrimethylammonium (Scott, Nowell & Wilson, 1962). It was later reported by these investigators that after prolonged in vitro incubation of neostigmine with human plasma two metabolites were identified; these were not present when plasma had been previously incubated with dyflos (Nowell, Scott & Wilson, 1962b). The fact that no metabolites could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1966
1966
1996
1996

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…In addition to a difference in species, the problems of equating intensity of pharmacological action with plasma concentrations of drugs are well known (Koch-Weser, 1972). The importance of renal excretion to the elimination of both neostigmine and pyridostigmine is suggested by the fact that 40-60% of both neostigmine and pyridostigmine are excreted in the urine (Nowell, Scott & Wilson, 1962;Roberts, Thomas & Wilson, 1965;Birtley, Roberts, Thomas & Wilson 1966). Our results of prolonged duration of action of both drugs therefore are not surprising.…”
Section: Discussionsupporting
confidence: 57%
“…In addition to a difference in species, the problems of equating intensity of pharmacological action with plasma concentrations of drugs are well known (Koch-Weser, 1972). The importance of renal excretion to the elimination of both neostigmine and pyridostigmine is suggested by the fact that 40-60% of both neostigmine and pyridostigmine are excreted in the urine (Nowell, Scott & Wilson, 1962;Roberts, Thomas & Wilson, 1965;Birtley, Roberts, Thomas & Wilson 1966). Our results of prolonged duration of action of both drugs therefore are not surprising.…”
Section: Discussionsupporting
confidence: 57%
“…3-OH PTMA and glucuronide in liver after administration of neostigmine It has previously been shown that after intramuscular administration of neostigmine more than 90% of the radioactivity in liver is present as metabolite (Roberts et a., 1965b). In view of the results currently reported, it was considered important to determine to what extent the metabolite in liver is present as free and conjugated 3-OH PTMA.…”
Section: Distribution In Tissuesmentioning
confidence: 99%
“…Estimation of pyridostigmine and its metabolite Urine and extracts of blood and liver were estimated for total radioactivity and for radioactive metabolite, using paper electrophoresis as described by Roberts et al (1965b). The radioactivity separated into two distinct bands; counts recorded between 10 and 13 cm from the origin are a measure of pyridostigmine and those recorded between 5 and 9 cm are a measure of metabolite (Birtley et al, 1966).…”
Section: Methodsmentioning
confidence: 99%